Dr. Tiago Baptista-Fernandes — Deep Plane Facelift — Lisbon - Baptista-Fernandes, Tiago (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Tiago Baptista-Fernandes, practicing in Lisbon, Portugal. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003133; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; portugal; lisbon